Радиационные нанотехнологии модификации модельных кристаллов электронными возбуждениями: 1. Локализация электронных возбуждений и подпороговое дефектообразование - Огурцов, Александр Николаевич (НТУ "ХПИ", 2005)
The article is devoted to the radiation technologies of lattice modification of model crystals of rare gases, with a focus on processes of subthreshold radiation-induced defect formation, stimulated by exciton self-trapping. The proposed luminescence-kinetic technique of analysis of dose curves allows the numerical modeling of the elementary inelastic processes and provides the way for analytical control and certification of Xe, Kr, Ar and Ne crystals.
Keywords: кристаллическая решетка; инертный газ; атомарные криокристаллы; экситоны